Cymensifin A: a promising pharmaceutical candidate to defeat lung cancer via cellular reactive oxygen species-mediated apoptosis - Soares, Bruno Cesar Costa; Khine, Hnin Ei Ei; Sritularak, Boonchoo; Chanvorachote, Pithi; Alduina, Rosa; Sungthong, Rungroch; Chaotham, Chatchai (Frontiers in Pharmacology, 2024)
The upgrade of natural products for cancer treatment is essential since current anticancer drugs still pose severe side effects. Cymensifin A (Cym A) isolated from an orchid Cymbidium ensifolium has shown its potential to induce the death of several cancer cells; however, its underlying molecular mechanisms are hitherto unknown.Methods: Here, we conducted a set of in vitro preliminary tests to assess the cytotoxic effects of Cym A on non-small-cell lung cancer (NSCLC) cells (A549, H23, H292, and H460). A flow cytometry system and western blot analyses were employed to unveil molecular mechanisms underlying cancer cell apoptosis caused by Cym A.Results: Cym A at 25-50 μM caused the death of all NSCLC cells tested, and its cytotoxicity was comparable to cisplatin, a currently used anticancer drug. The compound induced apoptosis of all NSCLC cells in a dose-dependent manner (5-50 μM), proven by flow cytometry, but H460 cells showed more resistance compared to other cells tested. Cym Atreated H460 cells demonstrated increased reactive oxygen species (ROS) and downregulated antioxidants (catalase, superoxide dismutase, and thioredoxin). The compound also upregulated the tumor suppressor P53 and the pro-apoptotic protein BAX but downregulated pro-survival proteins (BCL-2 and MCL-1) and deactivated survival signals (AKT and ERK) in H460 cells. Cym A was proven to trigger cellular ROS formation, but P53 and BAX were 2fold more activated by Cym A compared to those treated with hydrogen peroxide. Our findings also supported that Cym A exerted its roles in the downregulation of nuclear factor erythroid 2-related factor 2 (a regulator of cellular antioxidant activity) and the increased levels of cleaved poly(ADP-ribose) polymerase (PARP) and cleaved caspase 3/7 during apoptosis.We propose that Cym A induces lung cancer cell death via ROS-mediated apoptosis, while the modulation of cellular ROS/antioxidant activity, the upregulation of P53 and BAX, the downregulation or deactivation of BCL-2, MCL-1, AKT, and ERK, and the increased cleavage of PARP and caspase 3/7, were the elucidated underlying molecular 3 mechanisms of this phytochemical. The compound can be a promising candidate for future anticancer drug development.